Distance Education in Social Work During the COVID-19 Pandemic: Changes and Challenges - Lischer, Suzanne; Caviezel Schmitz, Seraina; Krüger, Paula; Safi, Netkey; Dickson, Cheryl (Frontiers in Education, 2021)
The COVID-19 pandemic has had an extensive impact on the global higher education sector. In a written survey, staff and students at the Lucerne School of Social Work reported how they had coped with the challenges to their teaching respective learning situation. The initial survey was conducted during the lockdown in spring 2020, and the follow-up survey was performed in the period of relaxed sanitary measures in summer 2020. During the first wave of the survey, 51 employees and 225 students participated. In the follow-up survey, 28 employees and 117 students partook. Findings indicate that the increased workload created by the transition was stressful for both staff and students but overall was handled well. Staff and students who felt supported by the university management experienced less psychological distress. Since the outbreak of the pandemic, there has been an effort to develop hybrid forms of teaching. Because the social work curriculum contains building blocks that are difficult to implement in the form of distance learning, the transition posed challenges for both staff and students. During times of transition, university management must carefully assess the support needs of staff and students and take appropriate action.